2013
DOI: 10.1074/jbc.m113.453282
|View full text |Cite
|
Sign up to set email alerts
|

A Brucella Virulence Factor Targets Macrophages to Trigger B-cell Proliferation

Abstract: Background: PrpA is a Brucella B-cell lymphoproliferative virulence factor. Results: PrpA and its homologue in Trypanosoma cruzi bind to macrophages through nonmuscular myosin IIA (NMM-IIA) to trigger B-cell proliferation. Conclusion: Brucella exploits macrophage functions to evade the immune response. Significance: A bacterial and a protozoan pathogen share a similar immune evasion strategy during infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…We have recently shed some light into the molecular mechanism of PrpA. Although this virulence factor is a B-cell mitogen, we have shown that it actually targets CD11b + F4/80 + macrophages, where it is translocated during infection [7]. PrpA treated macrophages release soluble factor/s ultimately responsible for B-lymphocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shed some light into the molecular mechanism of PrpA. Although this virulence factor is a B-cell mitogen, we have shown that it actually targets CD11b + F4/80 + macrophages, where it is translocated during infection [7]. PrpA treated macrophages release soluble factor/s ultimately responsible for B-lymphocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Brucella to establish chronic infections in the face of an ongoing immune response, suggests the existence of bacterial virulence factors with immunomodulatory effects. We have previously described a Brucella abortus virulence factor ( prpA, for Proline Racemase Protein A) that i) is secreted during infection, ii) interacts with NMMII-A in macrophages and iii) induces the release of soluble factors responsible for B-cell proliferation in vitro [7, 8]. We also showed that prpA is required for the establishment of the chronic phase of infection in mice [8].…”
Section: Introductionmentioning
confidence: 99%
“…B. abortus has the ability to enter and replicate inside mammalian cells (Gorvel & Moreno, 2002), which enables immune evasion and can reduce efficacy of antimicrobial therapies. There are several molecular features of the B. abortus cell that play a role in its ability to infect and replicate in mammalian hosts (Atluri et al, 2011, Batut et al, 2004, Byndloss & Tsolis, 2016, Celli, 2006, de Figueiredo et al, 2015, Gorvel, 2008, including smooth lipopolysaccharide (Lapaque et al, 2005, Cardoso et al, 2006, Conde-Alvarez et al, 2012, Smith, 2018, the type IV secretion system (Byndloss & Tsolis, 2016, O'Callaghan et al, 1999, Delrue et al, 2001, den Hartigh et al, 2008, and secreted protein effectors (de Barsy et al, 2011, Myeni et al, 2013, Spera et al, 2013. Here, we report a functional and structural analysis of envelope integrity protein A (EipA), a protein required for B. abortus envelope stress resistance and infection.…”
Section: Introductionmentioning
confidence: 91%
“…B. abortus has the ability to enter and replicate inside mammalian cells (1), which enables immune evasion and can reduce efficacy of antimicrobial therapies. There are several molecular features of B. abortus that play a key role in its ability to infect hosts (1)(2)(3)(4)(5)(6)(7)(8), including smooth lipopolysaccharide (SLPS) (9)(10)(11)(12), the type IV secretion system (6,(13)(14)(15), and secreted protein effectors (16)(17)(18)(19). Here, we report a functional and structural analysis of envelope integrity protein A (EipA), a protein required for B. abortus envelope stress resistance and infection.…”
Section: Introductionmentioning
confidence: 99%
“…B. abortus has the ability to enter and replicate inside mammalian cells (Gorvel and Moreno, 2002), which enables immune evasion and can reduce efficacy of antimicrobial therapies. There are several molecular features of the B. abortus cell that play a role in its ability to infect and replicate in mammalian hosts (Batut et al, 2004;Celli, 2006;Gorvel, 2008;Atluri et al, 2011;de Figueiredo et al, 2015;Byndloss and Tsolis, 2016), including smooth lipopolysaccharide (Lapaque et al, 2005;Cardoso et al, 2006;Conde-Alvarez et al, 2012;Smith, 2018), the type IV secretion system (O'Callaghan et al, 1999;Delrue et al, 2001;den Hartigh et al, 2008;Byndloss and Tsolis, 2016) and secreted protein effectors (de Barsy et al, 2011;Myeni et al, 2013;Spera et al, 2013). Here, we report a functional and structural analysis of envelope integrity protein A (EipA), a protein required for B. abortus envelope stress resistance and infection.…”
Section: Introductionmentioning
confidence: 99%